2018
DOI: 10.18632/oncotarget.24048
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-495 suppresses osteosarcoma invasion and migration by targeting HSP90AA1

Abstract: MiR-495 is a tumor-suppressive microRNA that participates in tumor progression in human cancers. However, its expression and biological function in osteosarcoma remains unknown. In this study, we firstly found that miR-495 is markedly downregulated in both osteosarcoma tissues and cell lines. Then we demonstrated that miR-495 suppresses the invasion and metastasis of osteosarcoma cells in vitro through inhibiting epithelial to mesenchymal transition. Function of miR-495 in vivo was also examined in mice xenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…High HSP90 expression in patients with cancer may result in a poor prognosis and low survival rate [36]. Studies have shown that microRNA-495 inhibits the invasion and migration of osteosarcoma by targeting HSP90AA1 [37]. Similarly, our findings showed that miR-302c-5p targeted HSP90AA1.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…High HSP90 expression in patients with cancer may result in a poor prognosis and low survival rate [36]. Studies have shown that microRNA-495 inhibits the invasion and migration of osteosarcoma by targeting HSP90AA1 [37]. Similarly, our findings showed that miR-302c-5p targeted HSP90AA1.…”
Section: Discussionsupporting
confidence: 73%
“…As a molecular chaperone, HSP90 binds to various intracellular 'client proteins', such as EGFR, RAF-1, B-RAF and ERK1/2 AKT, HER2, EGFR and CDK4, to maintain their structural stability and activity [34][35][36][37]. Studies have shown that EGFR is a client protein of HSP90, and their interaction is critical for maintaining the stability of the receptor and for the growth of EGFR-dependent cancers [38].…”
Section: Discussionmentioning
confidence: 99%